PENERAPAN KLAUSULA BAKU PADA PERJANJIAN PENGIKATAN JUAL BELI APARTEMEN SAHID RESIDENCE OLEH PENGEMBANG BERDASARKAN UNDANG UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi Putusan Nomor 53/PDT.G/2016/PN.JKT.PST Juncto Putusan Nomor 641/PDT/2016/PT.DKI) - Jessica Francis Gunawan; Siti Nurbaiti (Jurnal Hukum Adigama, 2020)
Accommodation is one of the physiological human needs that are required for survival. In Indonesia, the accommodation type available for its people are apartments.  There are several essential steps to be done prior to purchasing an apartment, such as Purchase Binding Agreements, which includes Standardized contract or Standardized Agreement. The written agreements are commonly created one-sidedly by the supplier and customers are often only accepting the agreements as they are unable to reject or to revise the content of the said agreements due to many unfamiliar vocabularies and often without any further explanations. This has put many customers into great disadvantages.Tiur Simamora is one of the victim of the above issue and is still unable to obtain the Deed of Sale and Purchase until the present time. The supplier included numerous unfamiliar vocabularies in the written agreement and did not include the specific date for the release of Deed of Sale and Purchase. While this has caused significant disadvantages for Simamora, the verdict of the District Courts ruled that the supplier was acquitted. According to the court, the supplier is not guilty by using many unfamiliar law terms in the agreement. However, the supplier has violated the Consumer Law and Simamora’s right as a consumer. Simamora’s case has been recorded by the District Courts under the case number: 53/PDT.G/2016/PN.JKT.PST.